Optimization of geometric thinking through interactive worksheets: a scoping review - Oktaviyanthi, Rina; Kadun, Selvi (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2025)
Geometric thinking is a crucial aspect of mathematics education, particularly in developing visualization skills, understanding geometric concepts, and problem-solving abilities. This study aims to explore the role of interactive worksheets (Lembar Kerja Peserta Didik, LKPD) in optimizing geometric thinking through a scoping review. Using a scoping review approach, a search was conducted in the credible Google Scholar database with the keywords “Interactive Worksheets,” “Geometric Thinking,” and “Mathematics Education.” The study specifically focused on research conducted in the context of Indonesia to understand the local implementation and outcomes. Articles were selected through abstract screening, full-text reading, and the application of inclusion criteria. The findings reveal that interactive worksheets significantly enhance students' geometric thinking by leveraging elements such as gamification, dynamic visualization, and technology-based interactive exercises. Research trends in Indonesia are dominated by experimental design and technological development, yet gaps persist, including a lack of long-term trials, limited focus on primary education, and insufficient diversity in the indicators of geometric thinking. This study recommends further research employing longitudinal approaches, exploring cutting-edge technologies such as AI and AR, and developing worksheets tailored to various educational levels. This study provides comprehensive insights into the potential of interactive worksheets to support the development of geometric thinking in the Indonesian context while identifying challenges that need to be addressed to enhance their effectiveness in mathematics education.